Covalent Triazine Frameworks as Metal Free Catalysts for the Oxidative Coupling of Amines to Imines. Issue 17 (2nd May 2019) - Zheng, He; Shi, Song; Wang, Xinhong; Zhao, Li; Zhu, Guozhi; Liu, Meng; Gao, Jin; Xu, Jie
Abstract: Covalent triazine frameworks (CTFs) were reported as heterogeneous catalysts for the oxidative coupling of benzylamines to imines. The CTFs with different monomers were characterized by TEM, XRD, FT‐IR, XPS, ICP etc. The CTFs showed good performances in various amines coupling and good stability for recycle reactions. High activities of the CTFs for amines coupling were attributed to the triazine structure and unique nature itself. ReactIR was used to investigate the catalytic process and two reaction routes were put forward according to the results. Abstract : Covalent triazine frameworks (CTFs) are reported as a class of metal free catalysts for the oxidative coupling of amines to imines. All the CTFs prepared with different monomers showed good performances in coupling of various amines. And the catalyst also showed good stability for recycle reactions. The triazine structure and unique properties of CTFs were believed to responsible for the high catalytic activities.